STUDI TUTUPAN TERUMBU KARANG DI PERAIRAN PULAU UNGGEH KECAMATAN BADIRI KABUPATEN TAPANULI TENGAH SUMATERA UTARA - Azwir Siregar; Budi Utomo; Zulham Apandy Harahap (AQUACOASTMARINE, 2018)
Unggeh island is administratively located in Sitardas Village, BadiriSubsistrict Tapanuli Tengah Regency. Exposure to the sea floor south, west, and north of Unggeh Island is overgrown by coral reef. Coral reef ecosystem is one of the coastal resources that are highly vulnerable to damage, especially those caused by human behavior. This research held on April 2017. This research aimed to know percent cover and the condition of coral reef ecosystem in the Unggeh Island. This research using Underwater Photo Transect (UPT) method. From this research results obtained 17 types of coral lifeform namely Acropora Branching,Coral Branching, Coral Encrusting, Coral Mushroom, Soft Coral, CoralSubmassive, Coral Massive, Makro Algae, Halimeda, Coral Foliose, Dead Coral with Algae, Dead Algae, Sand, Silt , Rubble, Turf Algae and Others, with were dominated by Dead Coral with Algae (DCA). The cover percentage of coral in the first station was 25,4 %, in the second station was 12,33 % and in the third station was 28,54 % with an average value was 22,09 % and coral reef condition in Unggeh Island was bad status.Keywords: Coral Reef Ecosystem, Unggeh Island, Percentage of CoralReef, Underwater Photo Transect (UPT)